IL-34 Suppresses Candida albicans Induced TNFα Production in M1 Macrophages by Downregulating Expression of Dectin-1 and TLR2 - Rong Xu; Hong-Fan Sun; David W. Williams; Adam V. Jones; Ali Al-Hussaini; Bing Song; Xiao-Qing Wei (Journal of Immunology Research)
Candida albicans is a fungus that is an opportunistic pathogen of humans. Normally, C. albicans exists as a harmless commensal and does not trigger inflammatory responses by resident macrophages in skin mucosa, which may be caused by a tolerance of skin macrophage to C. albicans. IL-34 is a recently discovered cytokine, constitutively expressed by keratinocytes in the skin. IL-34 binds to the receptor of M-CSF, thereby stimulating tissue macrophage maturation and differentiation. Resident macrophages exhibit phenotypic plasticity and may transform into inflammatory M1 macrophages for immunity or anti-inflammatory M2 macrophages for tissue repair. M1 macrophages produce higher levels of inflammatory cytokines such as TNFα in response to C. albicans stimulation. In this study, it was demonstrated that IL-34 attenuated TNFα production by M1 macrophages challenged with heat killed Candida (HKC). The molecular mechanism of IL-34 mediated suppression of HKC induced TNFα production by M1 macrophages was by the inhibition of M1 macrophage expression of key C. albicans pattern recognition receptors (PPRs), namely, Toll-like receptor (TLR) 2 and Dectin-1. The results of this study indicated that constitutive IL-34 expressed by skin keratinocytes might suppress resident macrophage responses to C. albicans colonisation by maintaining low levels TLR2 and Dectin-1 expression by macrophages.